Pak1ip1 Loss-of-Function Leads to Cell Cycle Arrest, Loss of Neural Crest Cells, and Craniofacial Abnormalities - Panoutsopoulos, Alexios A.; De Crescenzo, Angelo Harlan; Lee, Albert; Lu, Amelia MacKenzie; Ross, Adam P.; Borodinsky, Laura N.; Marcucio, Ralph; Trainor, Paul A.; Zarbalis, Konstantinos S. (Frontiers in Cell and Developmental Biology, 2020)
Neural crest cells comprise a transient progenitor cell population of neuroepithelial origin that contributes to a variety of cell types throughout vertebrate embryos including most mesenchymal cells of the cranial and facial structures. Consequently, abnormal neural crest cell development underlies a variety of craniofacial defects including orofacial clefts, which constitute some of the most common birth defects. We previously reported the generation of manta ray (mray) mice that carry a loss-of-function allele of the gene encoding the preribosomal factor Pak1ip1. Here we describe cranioskeletal abnormalities in homozygous mray mutants that arise from a loss of neural crest cells soon after their specification. Our results show the localized loss of cranial neural crest cells in the developing frontonasal prominences is caused by cell cycle arrest and cell death. In addition, and consistent with deficits in ribosome biosynthesis, homozygous mray mutants display decreased protein biosynthesis, further linking Pak1ip1 to a role in ribosome biogenesis.